Match analysis of elite adolescent team handball players - Chelly, M. S.; Hermassi, S.; Aouadi, R.; Khalifa, R.; van den Tillaar, R.; Chamari, K.; Shephard, R. J. (The Journal of Strength and Conditioning Research, 2011)
The purposes of this study were to examine the activity profile of elite adolescent players during regular team handball games and to compare the physical and motor performance of players between the first and second halves of a match. Activity patterns (video analysis) and heart-rate (HR) responses (telemetry) were monitored in top national-division adolescent players (18 men, aged 15.1 ± 0.6 years) throughout 6 regulation games (25-minute halves with a 10-minute interval). The total distance covered averaged 1,777 ± 264 m per game (7.4% less in the second than in the first half, p > 0.05). Players ran 170 ± 24 m at high intensity and 86 ± 12 m at maximal speed, with 32 ± 6 bouts of running (duration 2.3 ± 0.3 seconds) at speeds > 18 km/h; they stood still for 16% of the playing time. The mean HR during play was 172 ± 2 b·min-1 (82 ± 3% of maximal HR). Blood lactate concentrations at the end of the first and second halves were 9.7 ± 1.1 and 8.3 ± 0.9 mmol/L, respectively (difference p < 0.05). We conclude that adolescent handball players cover less distance and engage in fewer technical actions in the second half of a match. This indicates that team handball is physiologically very demanding. The practical implication is that coaches should seek to sustain performance in the second period of a game by modifying playing tactics and maximizing both aerobic and anaerobic fitness during training sessions.